Successful ablation of a right atrium−axillary ventricular accessory pathway associated with Wolff‐Parkinson‐White syndrome. Issue 12 (26th August 2017) - Yuan, Yuan; Long, Deyong; Dong, Jianzeng; Tao, Ling; Ma, Changsheng
Abstract: We report a case of a patient with right axillary ventricular. Similar congenital anomaly of the right atrium was reported as "right appendage diverticulum or right atrial diverticulum." However, this independent chamber has its own annulus, synchronizes with the right ventricular, and generates large ventricular potential. Under the guidance of the CARTO mapping system (Biosense Webster, Diamond Bar, CA, USA), a right atrioventricular accessory pathway associated with type B Wolff‐Parkinson‐White syndrome was ablated successfully. This pathway was close to the annulus of the axillary ventricular. The patient remained free of arrhythmia at 1‐year follow‐up.